Durian leather: development, properties and storage stability - Jaswir, Irwandi; Che Man, Yaakob (Wiley-Blackwell Publishing, 1996)
Three formulations of durian leather were developed and evaluated for their physicochemical, microbiological, sensory properties and storage stability. Proximate composition is reported. Vitamin C contents of the leather were relatively high and ranged between 21.6–26.6 mg/100 g. Water activity (Aw) of all formulations ranged between 0.57–0.62 and caloric content, 431–473 Kcal/100 g. After 12 weeks’ storage, all durian leather formulations were stable and showed low mold counts. The results from sensory evaluation revealed that the three formulations were acceptable in all attributes studied.